Rancang Bangun Sistem Informasi Manajemen dan Monitoring Aset IT Laboratorium Komputer Berbasis Web - Putra, Dwipa Junika (J-SIGN (Journal of Informatics, Information System, and Artificial Intelligence), 2025)
This research aims to develop a web-based IT asset management and monitoring information system for the Informatics computer laboratory. The system is designed to address issues such as manual inventory recording, inadequate reporting, non-integrated asset management processes, and limitations in real-time monitoring. The system includes a reporting form menu for IT assets in the computer laboratory that experience issues or damage. Users can submit reports through the application, which is designed with a user-friendly interface, allowing the reports to be forwarded to the laboratory manager for further inspection. The system not only provides more efficient inventory management features but also ensures transparency in reporting asset conditions. Employing the Waterfall methodology, the research encompasses the stages of requirement analysis, system design, implementation, testing, and maintenance. Key features include asset inventory recording with QRCode integration, detailed inventory tracking, periodic asset condition monitoring, and systematic mechanisms for asset damage reporting. This system is expected to enhance efficiency, accuracy, transparency, and ease in IT asset management, aligning with the operational needs of a modern, effective, efficient, and technology-driven laboratory.